EFFECT OF WATER ON METAL-SILICATE PARTITIONING OF SIDEROPHILE ELEMENTS: A HIGH PRESSURE AND TEMPERATURE TERRESTRIAL MAGMA OCEAN AND CORE FORMATION - Righter K.; Drake M.J. (My University, 1999)
Recent proposals of metal-silicate equilibrium at the base of a deep hydrous magma ocean are based on experimental data obtained under anhydrous conditions. We have undertaken a series of experiments at 10 kbar and 1300°C, designed to isolate the effect of dissolved water on the partitioning of the siderophile elements Ni, Co, Mo, W, and P between metal and hydrous silicate liquid. These experiments show that partition coefficients for Ni, Co, Mo and W remain unchanged under hydrous conditions up to ~4.0 wt.% dissolved H2O, whereas those for P remain unchanged only up to ~1.5 wt.% dissolved H2O, above which they increase. Such results indicate that the proposal of a deep hydrous magma ocean for the early Earth is robust across a range of water contents, but the highly charged cation, P, becomes more siderophile at high water contents. Predictive expressions for metal-silicate partitioning from our earlier studies have been augmented with new metal-silicate partition coefficient data. Earlier conclusions that terrestrial upper mantle abundances of Ni, Co, Mo, W, and P are consistent with metal-silicate equilibrium at the base of a deep hydrous magma ocean remain robust with the addition of these new data. These results have two implications for the earliest history of the Earth and its subsequent evolution. First, the high temperature and pressure conditions for both the Earth and the Moon are consistent with the thermal state of the early Earth expected in a giant impactor scenario for the origin of the Moon. Second, wet accretion of the Earth provides an alternative source of Earth's current atmosphere and hydrosphere, and would allow oxidation of originally reduced planetary building blocks.
Keywords: PARTITIONING; MAGMA OCEANS; EARTH-MOON COUPLE; ACCRETION; SIDEROPHILE ELEMENTS